Do Microtakaful Schemes as Risk Management Tools Contribute to Halal Small Business Sustainability? Evidence from Malaysia - Jaiyeoba, Haruna Babatunde; Moha Asri, Abdullah; Wan Mohd Naziman, Wan Ahmad; Fernando, Yudi (IIUM Press, 2022)
Microtakaful schemes have become increasingly crucial for risk management among halal small businesses. However, little is known about which of the schemes offered contribute to halal small business sustainability. Hence, this study intends to ascertain whether microtakaful schemes as risk management tools contribute to halal small business sustainability. This research adopts a quantitative research design by way of survey methodology to obtain data from halal small business owners and managers in Klang Valley, Malaysia. Additionally, exploratory factor analysis (EFA), confirmatory factor analysis (CFA), and structural equation modelling (SEM) were used to uncover which of the microtakaful schemes significantly contribute to halal small business sustainability. The results show that disability and family microtakaful schemes are positively and significantly related to halal small business sustainability. Whereas property and health microtakaful schemes are found to be positively, but insignificantly related to halal small business sustainability. Meanwhile, our findings on property and family microtakaful schemes reveal that more awareness and education should be prioritised by microtakaful operators.